The construction of collective identity in the British Parachute Regiment: a storytelling approach - Thornborrow, Thomas (2005)
The aim of this thesis is to illustrate how stories and extracts from stories can be used to investigate issues centred on organisational identity in the British Parachute Regiment, the `tribe' at the centre of this research. This thesis employs a narratological approach (Brown, 2001) in an autoethnographic study (Ellis and Bochner, 2000) in which I myself, as a member of the `tribe' and as a scholar, am centrally implicated. By adopting this methodology the thesis includes a reflexive examination of me as a Paratrooper and as an emergent scholar. These identities can be understood as two constituents of my own `parliament of selves' (Mead, 1934). By using myself as `subject' and conducting an analysis of my own `internal soliloquy' (Athens, 1994), I was able to frame a study to explore and analyse my methodology, and to illuminate the processes of autoethnographic research on which I was embarked by reference to notions of reflexivity, paradigm incommensurability and representation. The resultant story of my research is an interpretive account, constructed between the `polyphonic' voices of my brother Paratroopers who volunteered their stories as part of my research, and myself. Data collection involved interviewing 68 other Paratroopers for between 30 and 120 minutes using a semi-structured interview schedule, either at their place of work or in their homes. These interviews were taped, fully transcribed and analysed using a form of grounded theory. The interviews were conducted with three interconnected parts of the `tribe' - full time serving soldiers of the Parachute Regiment, part-time members of the Territorial Battalion, and members of an extended `brotherhood' of retired Paratroopers who were active members of the Parachute Regiment Association (PRA). I analyse my data using two theoretical frameworks. First, I make use of Albert and Whetten's (1985) understanding of organisational identity to interpret what Paratroopers believed to be central, distinctive and enduring about their Regiment and themselves. In so doing I also consider issues of image (Dutton and Dukerich, 1991; Dutton et al., 1994) and reputation (Fombrun and Shanley, 1990). Second, I employ Elsbach's (1999) model of organisational identification (identification; disidentification; schizo-identification; and neutral-identification) to analyse individual-organisation relationships. In particular, I focus on what I refer to as `strong', `weak' and the `dark side' of organisational identification (cf. Dukerich, et al., 1999). I then conduct four readings of the data in which I have addressed: (1) issues of representation and credibility in autoethnographic research; (2) organisational narcissism (Brown, 1997) (3) the symbolism inherent in the attire worn by Paratroopers both at work and play; and (4) the `implied contract' between Paratroopers and the Regiment (Watson, 2001) with particular reference to ‘breaches' and `violations, ' which in turn affect the strength of organisational identification. Finally, I draw some conclusions regarding my research contribution.